Spelen met religie in hedendaags theater - de Groot, Kees (Religie & Samenleving, 2011)
Contemporary theatre sometimes uses religious language, symbols and poses, including elements derived from the Christian tradition. The question is what these references mean: how serious is the courtship with religion? I have selected four productions with unmistakable religious elements. I used the tools of the anthropological informed study of liturgy to test whether these could help to produce an account of the liturgical quality of these shows and performances. Two conclusions could be drawn. Firstly, in some instances the boundary between performers and audience is made fluid. This induces a development towards an event. Secondly, in some cases the show includes the (collective) performance of rituals, but within the context of theatre. These theatrical approaches, constrained by the limitations inherent to professional secular theatre, facilitate a liturgical function of contemporary theatre. Apparently, it is possible to make analytical distinctions with respect to the liturgical quality of the productions, although the subjective element is never absent.